Identifying potential gray wolf habitat and connectivity in the eastern USA - van den Bosch, M.; Beyer, D.E.; Erb, J.D.; Gantchoff, M.G.; Kellner, K.F.; MacFarland, D.M.; Norton, D.C.; Patterson, B.R.; Price Tack, J.L.; Roell, B.J.; Belant, J.L. (Biological conservation, 2022)
Following federal protection in 1974, gray wolves (Canis lupus) partially recolonized former range in the western Great Lakes region, USA, yet remain absent from most of the eastern USA. Understanding potential for further recolonization requires quantifying remaining wolf habitat and habitat connectivity. We used recent snow tracking data from the western Great Lakes region to create an ensemble distribution model to estimate areas of habitat large enough to support gray wolf populations in the eastern USA. We then modeled cost-weighted distances between these areas and circuit connectivity to identify potential linkages. Our final distribution model had good performance (Receiver Operator Characteristic = 0.87) and suggests wolves selected against areas with greater human population densities and proportions of agricultural land. Gray wolves currently occupy about 4 % of their historical range in the eastern USA, which represents 12 % of the area estimated to remain suitable. We estimated 35 % of former range is currently suitable for wolves, and 18 % of these suitable areas are protected, mostly under state and federal jurisdictions. We identified five unoccupied areas where wolves could establish viable populations ranging from 18,110 to 725,488 km2. Connectivity between these areas and current wolf range is limited primarily by the Great Lakes and extensive agriculture in the Midwest USA. Most core habitat areas and priority linkages cross state or country borders, highlighting the importance of interjurisdictional cooperation. Our estimates of remaining suitable range and the potential for recolonization provide a baseline for the development of policies on gray wolf conservation in the eastern USA. •About 65 % of gray wolf historical range in the eastern USA is now unsuitable.•Wolves selected against areas with high human and agriculture densities.•Five areas that could support wolf populations remain, but connectivity is limited.•Proportions of protected area are higher in occupied than in potential wolf range.•Human tolerance is likely crucial to further wolf recolonization or reintroduction.